Sex Control in Aquaculture - Han‐Ping Wang; Francesc Piferrer; Song‐Lin Chen (John Wiley & Sons Ltd., 2025)
This book was motivated by an increasing, strong need for the control of sex ratios and monosex production knowledge and technology by the rapid growing global aquaculture industry. Currently, aquaculture – the fastest growing food‐producing sector – contributes about 50% of the world’s food fish, based on the Food and Agriculture Organization (FAO) latest reports. Sex control in aquaculture serves different purposes. First and foremost, a wide spectrum of aquacultured species show sexual dimorphism in growth and ultimate size, whereby one sex grows faster than the other or attains a larger size. Thus, there are important benefits in rearing only the fastest‐growing sex or monosex production. Second, in some species, precocious maturation and uncontrolled reproduction need to be prevented. Third, some negative impacts of reproduction on product quality or disease resistance need to be prevented in some species. Fourth, in sex‐changing hermaphrodites, sex ratio control can benefit broodsrock management. Finally, there are some species where the gonads or gametes of females have special economic value, e.g., caviar.